1997
DOI: 10.1051/aas:1997179
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DQ Serpentis and DT Serpentis as symbiotic stars

Abstract: Abstract. Optical and near infrared spectroscopy of the stars DQ Ser and DT Ser are presented. DQ Ser shows a late-type continuum (M3 − M5) with emission lines of Balmer series, HeI, HeII, [OIII], OI and CaII triplet while DT Ser presents a earlier spectral type with emission of Balmer lines, HeI, HeII and [OIII]. DT Ser is a faint V = 15.4 star 5 arcsec from a V = 12.8 G companion. We suggest it to be a yellow symbiotic star.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 9 publications
(10 reference statements)
1
42
0
Order By: Relevance
“…M6 spectral type of cool component and D' IR type from [172] are not reliable, as M6 does not agree with IR colours (JHK) and authors do not follow original definition of D'. s21=DT Ser Considered as symbiotic in [49,50]: emission spectrum of H i, He i and other lines with ionization potential up to 54.4 eV plus G? [49] or G2-K0 III-I [50] cool component.…”
Section: =R Aqrmentioning
confidence: 99%
“…M6 spectral type of cool component and D' IR type from [172] are not reliable, as M6 does not agree with IR colours (JHK) and authors do not follow original definition of D'. s21=DT Ser Considered as symbiotic in [49,50]: emission spectrum of H i, He i and other lines with ionization potential up to 54.4 eV plus G? [49] or G2-K0 III-I [50] cool component.…”
Section: =R Aqrmentioning
confidence: 99%
“…Except for GX 1+4 (Jablonski et al 1997;Chakrabarty & Roche 1997), none of the neutron starYcontaining symbiotic stars produce optical flickering (e.g., Sokoloski et al 2001), which is common in CVs, or show Balmer or He ii emission lines (Masetti et al 2007b). The presence of optical flickering and Balmer and He ii emission lines from RT Cru (Cieslinski et al 1994) suggests that it therefore contains an accreting WD rather than a neutron star. Reddening estimates from optical spectra and infrared magnitudes (coupled with the assumption that the radius of the M5 III red giant is about 0.5 AU; van Belle et al 1999) suggest that RT Cru is between 1.5 and 2 kpc away (J.…”
Section: Introductionmentioning
confidence: 99%
“…The GCVS lists the variability range as 13.9 ≤ m pg ≤ 13.2. Cieslinski et al (1997) have shown that the symbiotic star is indeed a faint star (B = 15.91, V = 15.40) about 5 arcsec from a much brighter field star (that we have measured at B = 13.550 ± 0.003, V = 12.772 ± 0.014, U − B = +0.109 ± 0.004, V − R = +0.462 ± 0.017 and R − I = 0.475 ± 0.006). The B = 13.55 of the nearby field star (not variable between the three observations we have obtained in separate nights) well matches the mean brightness of DT Ser listed in the GCVS.…”
Section: V471mentioning
confidence: 99%
“…The GCVS gives a variability range 16.0 ≤ m pg ≤ 13.9. Cieslinski et al (1997) list V = 14.5 and B − V = +1.23, while MHZ reports V = 14.94 and B − V = +1.34.…”
Section: V471mentioning
confidence: 99%
See 1 more Smart Citation